Occurrence of glycosidically bound flavour compounds in hops, hop products and beer - Kollmannsberger, Hubert; Biendl, Martin; Nitz, Siegfried (BrewingScience, 2006)
Glycosidically bound flavour compounds of hops are considered to contribute to the hop flavour in beer. Therefore, different hop varieties and hop products were analyzed for their glycoside content. During extraction with supercritical CO2 almost all of the hop glycosides remain in spent hops. After ethanol extraction, glycosides could be detected in both the ethanol tannin extract and the ethanol pure resin extract. In all examined varieties an enrichment of the sensorially important glycosides of monoterpene alcohols (e.g. linalool) and nor-carotenoids could be observed in the ethanol pure resin extracts. Some of these glycosides could be detected in hopped beer, where they could act as precursors for the organoleptically active linalool. This could be confirmed by a rise in free linalool in a stored beer brewed with a re-extracted ethanol pure resin extract containing linalyl glycoside, compared to a beer brewed with a glycoside-free hop preparation. The strongly flavour-active β-damascenone could also be liberated from hop glycosides, but hops seem not to be the only source for this ketone.